2018
DOI: 10.1111/neup.12459
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological and genetic association between epithelioid glioblastoma and pleomorphic xanthoastrocytoma

Abstract: Epithelioid glioblastoma (eGBM) is a rare variant of GBM which was adopted in the 2016 WHO classification. eGBM and pleomorphic xanthoastrocytoma (PXA) sometimes show overlapping features histologically and genetically, such as epithelioid pattern and a highly frequent V600E mutation in the gene for vRAF murine sarcoma viral oncogene homolog B1 (BRAF), respectively. Accurate diagnosis of these rare tumors is challenging according to the new criteria in the revised 2016 WHO classification. It is an urgent task … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 48 publications
2
22
0
Order By: Relevance
“…Further, BRAF p.V600E pLGG, especially in the context of co-occurring CDKN2A deletions (discussed further below), are significantly more likely to transform into HGG; an event which may occur 10-20 years after the initial diagnosis [142]. While not exclusive to this entity, transformation has been most commonly describe for pleomorphic xanthoastrocytoma which has been suggested to be within the same family as epithelioid GBM [4,63,210]. These "pleomorphic xanthoastrocytomalike" GBM carry a better prognosis compared to other GBM, but are still significantly worse when compared to pLGG [117].…”
Section: Braf Pv600ementioning
confidence: 99%
“…Further, BRAF p.V600E pLGG, especially in the context of co-occurring CDKN2A deletions (discussed further below), are significantly more likely to transform into HGG; an event which may occur 10-20 years after the initial diagnosis [142]. While not exclusive to this entity, transformation has been most commonly describe for pleomorphic xanthoastrocytoma which has been suggested to be within the same family as epithelioid GBM [4,63,210]. These "pleomorphic xanthoastrocytomalike" GBM carry a better prognosis compared to other GBM, but are still significantly worse when compared to pLGG [117].…”
Section: Braf Pv600ementioning
confidence: 99%
“…Next, we considered the possibility that our case may be PXA or GG. Several reports have assumed that E‐GBM and PXA are the same entity because of the similarity in the results of histologic and genetic analyses . Moreover, some studies have suggested that BRAF mutations might be related to the epithelioid features of high‐grade gliomas .…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have assumed that E-GBM and PXA are the same entity because of the similarity in the results of histologic and genetic analyses. 10,11 Moreover, some studies have suggested that BRAF mutations might be related to the epithelioid features of high-grade gliomas. 12 Thus, it is necessary to make these differential diagnoses based on both histopathologic and genetic analyses.…”
Section: Discussionmentioning
confidence: 99%
“…The similar high frequency of BRAF V600E in epithelioid glioblastomas and PXAs suggests that both tumors may belong to one family with divergent morphologic features [95,96]. In this context one interesting clinical case should be noted that reported an eGBM recurrence after the initial diagnosis of a PXA [97].…”
Section: Adult Brain Tumorsmentioning
confidence: 99%